A case report on unicentric form of Castleman’s disease (Indian Journal of Case Reports, 2020)
Castleman’s disease, also known as angiofollicular lymph node hyperplasia, is a heterogeneous group of lymphoproliferative disorders. It is a rare disease and difficult to diagnose preoperatively. Localized Castleman’s disease is almost always hyaline vascular variant type. We present the case of a 30-year-old male with swelling over the left side of the neck for 10 years which was diagnosed as Castleman’s disease on histopathology.